Mimicry of Central-Peripheral Immunity in Alzheimer's Disease and Discovery of Neurodegenerative Roles in Neutrophil - Park, Joseph; Baik, Sung Hoon; Mook-Jung, Inhee; Irimia, Daniel; Cho, Hansang (Frontiers in Immunology, 2019)
Neuroinflammatory roles of central innate immunity in brain parenchyma are well regarded in the progression of neurodegenerative disorders including Alzheimer’s disease (AD), however, the roles of peripheral immunity in central nervous system (CNS) diseases are less clear. Here, we created a microfluidic environment of human AD brains: microglial neuroinflammation induced by soluble amyloid-beta (Abeta), a signature molecule in AD and employed the environment to investigate the roles of neutrophils through the central-peripheral innate immunity crosstalk. We observed that soluble Abeta-activated human microglial cells produced chemoattractants for neutrophils including IL6, IL8, CCL2, CCL3/4, CCL5 and consequently induced reliable recruitment of human neutrophils. Particularly, we validated the discernable chemo-attractive roles of IL6, IL8, and CCL2 for neutrophils by interrupting the recruitment with neutralizing antibodies. Upon recruitment, neutrophils released inflammatory mediators such as MIF and IL2, detrimental to brain cells. We envision that targeting the crosstalk between central-peripheral immune community is a potential strategy to reduce immunological burdens in other neuroinflammatory CNS diseases.